Playing board games with mathematical self-concept to support early numeracy skill of 5-6 years old children. (February 2019) - Andika, W D; Akbar, M; Yufiarti,; Sumarni, Sri
Abstract: Many studies have found the benefits of playing board games is that it develops children's early numeracy. On the other hand, however, mathematical self-concept has an important role in developing early numeracy. This period of time has become a part of 36 participants of the activities of playing board game and mathematical self-concept is an important element in improving children's early numeracy. In this study, play activities board games from linear board games and circular board games and mathematical self-concepts with the experiment research design. The results show, playing linear board games better than circular board games (Fcount 5, 62) and the study has proven playing board game and mathematical self-concept significantly (Fcount 6, 69) can support early numeracy skill of 5-6 years old children. So, for supporting early numeracy skill, teacher must identify children's mathematical self concept to choose appropriate board games.